Candida Species Isolation from Hospitalized Patients with COVID-19—A Retrospective Study - Petros Ioannou; Diamantis P. Kofteridis; Konstantinos Alexakis; Christos Koutserimpas; Ioanna Papakitsou; Sofia Maraki; George Samonis (Diagnostics, 2022)
Coronavirus disease 2019 (COVID-19), a disease characterized by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has so far led to hundreds of millions of infections and millions of deaths. Fungal infections are known to complicate COVID-19 patients and are associated with significant morbidity and mortality. The aim of this study was to assess the incidence of positive cultures for Candida spp. among patients hospitalized with COVID-19, describe their characteristics and identify factors associated with overall mortality in this patient population. Hospitalized COVID-19 patients with Candida spp. isolation were retrospectively assessed and their clinical, laboratory and microbiological characteristics were assessed and evaluated. In total, 69 patients with COVID-19 had a positive culture for Candida spp., representing a rate of 4.5% among all hospitalized COVID-19 patients. Their median age was 78 years (IQR 67–85 years) and 44.9% were male. Hospitalized patients with COVID-19 and Candida spp. isolation who died were older, were more likely to have a diagnosis of dementia, and had higher Charlson comorbidity index, higher Candida score and higher 4C score. Candida score was identified with a multivariate logistic regression analysis model to be independently associated with mortality. The most commonly identified Candida species was C. albicans, followed by C. tropicalis and C. glabrata and the most common source was the urine, even though in most cases the positive culture was not associated with a true infection. Thus, Candida score may be used in COVID-19 patients with isolation of Candida spp. from different body specimens for mortality risk stratification.